Multiresistant bacteria in irrigation waters of the Chibunga River, Chimborazo, Ecuador - Guillén-Ferraro, Morella Lucia (2024)
The development of living beings depends on the health and chemical quality of the available water. In recent years, the importance of the environment in the spread of resistant and multi-resistant bacteria to antibiotics has been observed, a situation that has placed the problem of antibiotic resistance on a broader level and which is being studied from the perspective “One Health”. The objective of this work was to determine the presence of multi-resistant bacteria to antibiotics in irrigation water samples from the Chibunga river. Fourteen water samples of 100 mL each were collected in sterile containers and aseptically, were kept under refrigeration until analysis in the laboratory. Each sample was seeded by the surface seeding method on blood, cystine electrolyte deficient, MacConkey, Salmonella-Shigella and thiosulfate citrate bile sucrose agars, incubating in all cases at a temperature of 37 °C for a maximum time of 48 hours. The identification of bacterial colonies was carried out through physiological and biochemical tests according to the identification schemes indicated by MacFaddin. The resistance/sensitivity to antibiotics of the identified colonies was carried out by the disk diffusion method of Kirby Bauer. Two species of multi-resistant bacteria were identified, including strains of Morganella morgani and Plesiomonas shigelloides resistant to antibiotics of clinical use such as ceftazidime, aztreonam, ciprofloxacin, nalidixic acid and trimethoprim-sulfamethoxazole. The results show that the waters of Chibunga river harbor bacteria with multi-resistance to antimicrobials, representing a contamination risk of agricultural products harvested in its vicinity, as well as for the people who use these waters.